2013
DOI: 10.3892/mco.2013.209
|View full text |Cite
|
Sign up to set email alerts
|

Body weight changes in breast cancer patients following adjuvant chemotherapy and contributing factors

Abstract: Abstract. Weight gain commonly occurs in breast cancer patients who receive adjuvant chemotherapy. Weight gain may cause psychosocial stress and is associated with patient prognosis and survival. Several factors contributing to weight gain have been identified in Western populations. However, there was lack of information associated with body weight changes following adjuvant chemotherapy in Chinese breast cancer patients. To the best of our knowledge, this is the first such study to be conducted in the Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
3
20
1
8
Order By: Relevance
“…The larger prospective studies of the National Cancer Institute, such as the Women's Healthy Eating and Living Study (Wang et al., ) conducted in >3,000 early‐stage BC survivors, and the Health, Eating, Activity, and Lifestyle Study, which has enrolled about 1,200 women with early‐stage BC, have reported weight changes similar to those observed in the present study. In both of those studies, chemotherapy was significantly associated with weight gain up to 6 years after diagnosis.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The larger prospective studies of the National Cancer Institute, such as the Women's Healthy Eating and Living Study (Wang et al., ) conducted in >3,000 early‐stage BC survivors, and the Health, Eating, Activity, and Lifestyle Study, which has enrolled about 1,200 women with early‐stage BC, have reported weight changes similar to those observed in the present study. In both of those studies, chemotherapy was significantly associated with weight gain up to 6 years after diagnosis.…”
Section: Discussionsupporting
confidence: 79%
“…Some studies have demonstrated a weight increase in pre-menopausal women, but not all investigations support this particular condition (Ingram & Brown, 2004;Vance et al, 2011). Other studies have demonstrated that the continued use of steroids during chemotherapy, to treat side effects like nausea and vomiting, is associated with significant weight gain during treatment (Demark-Wahnefried et al, 2001;Wang et al, 2014). Antracyclin-based chemotherapy (like most of the patients received in this cohort study) is also associated with less weight gain, but our findings are not consistent with that evidence (Trédan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ao comparar o peso das mulheres antes e após / durante o tratamento quimioterápico, ao contrário do que se esperava (ganho ponderal) 10,13,14,20,23 , observou-se média de peso semelhante entre os dois períodos, sem significância estatística, enquanto que pouco mais da metade das mulheres estudadas perderam peso durante tratamento quimioterápico, e a outra metade, um pouco menos, apresentou ganho ponderal.…”
Section: Discussionunclassified
“…Além disso, o tratamento quimioterápico é capaz de influenciar negativamente o estado nutricional, segundo os indicadores do Índice de Massa Corporal (IMC) [7][8][9][10] . Embora o tratamento auxilie no aumento da sobrevida livre da doença e da sobrevida global de mulheres com câncer de mama 9,11 , é capaz de acentuar os efeitos nutricionais adversos do câncer, com consequente esgotamento das reservas de nutrientes 12 , além de um preocupante fator como o estímulo ao ganho de peso 13,14 .…”
unclassified